2015
DOI: 10.1038/ng.3473
|View full text |Cite|
|
Sign up to set email alerts
|

Recurrent mTORC1-activating RRAGC mutations in follicular lymphoma

Abstract: Follicular lymphoma is an incurable B-cell malignancy1 characterized by the t(14;18) and mutations in one or more components of the epigenome2,3. Whilst frequent gene mutations in signaling pathways, including JAK-STAT, NOTCH and NF-κB, have also been defined2-7, the spectrum of these mutations typically overlap with the closely-related diffuse large B cell lymphoma (DLBCL)6-13. A combination of discovery exome and extended targeted sequencing revealed recurrent somatic mutations in RRAGC uniquely enriched in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
166
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(178 citation statements)
references
References 59 publications
7
166
0
5
Order By: Relevance
“…13 More recently, several studies have performed exome-based discovery sequencing on small sets of patients with FL, with subsequent extension sequencing of highly recurrent mutations in larger validation cohorts. [14][15][16][17] These approaches have confirmed the impact of mutations previously identified and revealed a number of recurrently mutated genes and pathways in FL, including histone modifiers, histone H1 genes, B-cell receptor signaling genes, STAT6, POU2F2, and others. Using a panel of 74 genes, Pastore et al 18 identified 7 recurrently mutated genes that added to the predictive ability of the standard clinical FL international prognostic index (FLIPI), resulting in the new m7-FLIPI.…”
Section: Introductionsupporting
confidence: 52%
“…13 More recently, several studies have performed exome-based discovery sequencing on small sets of patients with FL, with subsequent extension sequencing of highly recurrent mutations in larger validation cohorts. [14][15][16][17] These approaches have confirmed the impact of mutations previously identified and revealed a number of recurrently mutated genes and pathways in FL, including histone modifiers, histone H1 genes, B-cell receptor signaling genes, STAT6, POU2F2, and others. Using a panel of 74 genes, Pastore et al 18 identified 7 recurrently mutated genes that added to the predictive ability of the standard clinical FL international prognostic index (FLIPI), resulting in the new m7-FLIPI.…”
Section: Introductionsupporting
confidence: 52%
“…Somatically acquired mutations of ATP6V1B1 or the accessory subunit ATP6AP1 are detected in ~20% of follicular lymphoma (FL) 43, 44. These V‐ATPase mutations frequently co‐occur with mutations in the RRAGC gene encoding the Rag‐GTPase family member RagC which, with V‐ATPase and the V‐ATPase interaction partner Ragulator, form an amino acid “sensing” supercomplex which is required for mTORC1 activation 45.…”
Section: Dysregulation Of V‐atpase In Cancermentioning
confidence: 99%
“…These V‐ATPase mutations frequently co‐occur with mutations in the RRAGC gene encoding the Rag‐GTPase family member RagC which, with V‐ATPase and the V‐ATPase interaction partner Ragulator, form an amino acid “sensing” supercomplex which is required for mTORC1 activation 45. FL RRAGC mutations appear to be gain‐of‐function and promote inappropriate mTORC1 activity following amino‐acid depletion 44. Functional data are lacking, but V‐ATPase mutations may also promote inappropriate mTORC1 activation in FL.…”
Section: Dysregulation Of V‐atpase In Cancermentioning
confidence: 99%
“…More recently, recurrent mammalian target of rapamycin complex 1-activating RRAGC mutations in FL have been described. 19 This suggests that progression from t (14;18) 1 premalignant precursor cells to FL is likely the result of epigenetic alterations. 14,15 PTFL is also a lymphoma derived from GC cells, but without the characteristic t(14;18) translocation.…”
Section: Introductionmentioning
confidence: 99%